IMPLEMENTASI PERAGA SARIPATI PADA PEMBELAJARAN MATEMATIKA SISTEM AKAR PANGKAT TIGA: SDN GRUJUGAN LOR 2 JAMBESARI DARUSSHOLAH BONDOWOSO (Mitra Pendidikan, 2020)
Abstract in previous lessons, most students were less attracted to the materials root cubed. The findings of the pre study showed results of student learning is less satisfactory. This research was conducted to improve student learning outcomes through the use of fruit tree props QUINTESSENCE. Research conducted for 2 cycles, involving 24 grade VI SD Negeri Grujugan lor 2 Kecamatan Jambesari Sholah Darus Bondowoso on semester 1 year 2019 2020./Lesson. Research activities carried out by means of the use of fruit tree props QUINTESSENCE. The results showed increased significantly on the student learning outcomes, i.e. 95% student satisfaction. Based on the results of the study it can be concluded that the use of fruit tree props QUINTESSENCE is able to improve the learning outcomes of students of class VI SD Negeri Grujugan Lor 2.